Small changes in the length of diselenide bond-containing linkages exert great influences on the antitumor activity of docetaxel homodimeric prodrug nanoassemblies - Lingxiao Li; Shiyi Zuo; Fudan Dong; Tian Liu; Yanlin Gao; Yinxian Yang; Xin Wang; Jin Sun; Bingjun Sun; Zhonggui He (Elsevier, 2021)
Homodimeric prodrug-based self-assembled nanoparticles, with carrier-free structure and ultrahigh drug loading, is drawing more and more attentions. Homodimeric prodrugs are composed of two drug molecules and a pivotal linkage. The influence of the linkages on the self-assembly, in vivo fate and antitumor activity of homodimeric prodrugs is the focus of research. Herein, three docetaxel (DTX) homodimeric prodrugs are developed using different lengths of diselenide bond-containing linkages. Interestingly, compared with the other two linkages, the longest diselenide bond-containing linkage could facilitate the self-delivery of DTX prodrugs, thus improving the stability, circulation time and tumor targeting of prodrug nanoassemblies. Besides, the extension of linkages reduces the redox-triggered drug release and cytotoxicity of prodrug nanoassemblies in tumor cells. Although the longest diselenide bond-containing prodrug nanoassemblies possessed the lowest cytotoxicity to 4T1 cells, their stable nanostructure maintained intact during circulation and achieve the maximum accumulation of DTX in tumor cells, which finally "turned the table". Our study illustrates the crucial role of linkages in homodimeric prodrugs, and gives valuable proposal for the development of advanced nano-DDS for cancer treatment.